Intestinal obstruction secondary to infantile polyarteritis nodosa - Federico G Seifarth; Samuel Ibrahim; Steven J Spalding; Janet R Reid (Wolters Kluwer Medknow Publications, 2014)
Polyarteritis Nodosa (PAN) is a rare systemic necrotising vasculitis of medium and small-sized arteries. Patients typically present with systemic symptoms. Obstructive intestinal symptoms are described but usually resolve with treatment of the underlying vascular disease. We report a case of a one year old boy with multiple ischemic small bowel strictures secondary to infantile PAN, who was treated with resection of the affected segments by single port laparoscopy.